Adult acute myeloid leukemia patients with NUP98 rearrangement have frequent cryptic translocations and unfavorable outcome. Issue 8 (3rd July 2022) - Xie, Wei; Raess, Philipp W.; Dunlap, Jennifer; Hoyos, Cristina Magallanes; Li, Hongmei; Li, Peng; Swords, Ronan; Olson, Susan B.; Yang, Fei; Anekpuritanang, Tauangtham; Hu, Shimin; Wiszniewska, Joanna; et al.
Abstract: Acute myeloid leukemia (AML) with NUP98 rearrangement (AML- NUP98 ) has been uncommonly reported in adults, and its incidence in our institution is ∼2.5%. There were four men and five women with a median age of 49 years, among which six cases were de novo AML and three were therapy-related. Five cases were AML with minimal differentiation or without maturation, followed by four with monocytic differentiation . NUP98 rearrangement was confirmed in all cases by FISH, and five cases showed cryptic translocations. The median overall survival (OS) was 13 months, shorter than that of AML- NPM1 ( p < 0.05), and similar to that in AML- KMT2A patients in our institution. The unfavorable OS was further confirmed by comparing to AML patients in TCGA database. In conclusion, adult AML- NUP98 is associated with cryptic translocations and an unfavorable outcome. Our study suggests that incorporating the NUP98 probe into AML FISH panels are warranted to improve clinical management.